Advancing dye-sensitized solar cell performance with bifacial illumination: a novel Stack Formation Framework approach - AlSultan, Hussein A.; Shafie, Suhaidi; Hamidon, Mohd Nizar; Ismail, Ismayadi; Pandey, Shyam S.; Ahmad, Fauzan (Elsevier, 2024)
Dye-sensitized solar cells (DSSCs) are considered to be one of the promising photovoltaic devices in terms of low cost, low toxicity, and versatility. However, the issue of low power conversion efficiency (PCE) is still a main issue of those devices, especially in low light harvesting and the issue of electron–hole recombination that hinders the PCE of the device. This study aims to enhance the PCE by maximizing the light-harvesting without sacrificing the electron–hole separation by a novel approach of the Stack Formation Framework (SFF) for multi-layered Titanium Dioxide (TiO2) photoanodes in DSSCs by integrating bifacial illumination capabilities. The SFF method, leveraging both commercial and synthesized TiO2 pastes, now considers light absorption from both the front and rear sides of the device, aiming to harness the full potential of ambient light sources. Comparative analyses under varying illumination conditions reveal the T/sp-P25-T/sp (TPT) configuration's superior efficiency (6.1%) and (3.8%) PCE in front and back respectively, with a notable increase in overall theoretical photocurrent (Jsc) to (15.99 mA) and (9.32 mA) in front and back illumination respectively. When both sides are utilized using a reflective mirror, the PCE reaches (9.9%). This work underscores the potential of bifacial DSSCs in maximizing energy capture and conversion, setting a new benchmark for photoanode performance in photovoltaic applications.